2017
DOI: 10.1017/s1047951117001767
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil gelatinase-associated lipocalin reflects inflammation and is not a reliable renal biomarker in neonates and infants after cardiopulmonary bypass: a prospective case–control study

Abstract: Our results suggest that plasma and urinary neutrophil gelatinase-associated lipocalin values are not reliable indicators of impending acute kidney injury in neonates and infants after cardiac surgery with cardiopulmonary bypass. Inflammation may have a major impact on plasma neutrophil gelatinase-associated lipocalin values in infant cardiac surgery. Urinary neutrophil gelatinase-associated lipocalin may add little prognostic value over cardiopulmonary bypass time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
(87 reference statements)
0
9
0
Order By: Relevance
“…But in the cases experiencing longer cardiopulmonary bypass (CPB) time (≥75 min), uNGAL increases significantly as early as 2 hours after surgery. 26 KIM-1, a type 1 transmembrance protein, could not be detected in urine normally, but increases promptly after proximal tubular epithelial cells injury, boosting epithelial repair and phagocytosis. In a study with patients younger than 1 year old (including neonates), urinary KIM-1 at 6 hours after CPB has predictive power for AKI, with an AUC of 0.66.…”
Section: Proximal Tubular Cell Biomarkersmentioning
confidence: 89%
“…But in the cases experiencing longer cardiopulmonary bypass (CPB) time (≥75 min), uNGAL increases significantly as early as 2 hours after surgery. 26 KIM-1, a type 1 transmembrance protein, could not be detected in urine normally, but increases promptly after proximal tubular epithelial cells injury, boosting epithelial repair and phagocytosis. In a study with patients younger than 1 year old (including neonates), urinary KIM-1 at 6 hours after CPB has predictive power for AKI, with an AUC of 0.66.…”
Section: Proximal Tubular Cell Biomarkersmentioning
confidence: 89%
“…Neutrophils are the common type of leukocytes, and arrive rapidly to sites of acute inflammation, where they are responsible for phagocytosis and killing of invading pathogens (12). Neutrophil activation is known to trigger systemic inflammation and has been demonstrated to play a pivotal role in the inflammatory response induced by CPB (6, 13, 14). CPB triggers the activation of neutrophils in the complement cascade, inducing the secretion of polymorphonuclear elastase (PMN-E).…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophil activation can trigger systemic inflammation and has been recognized to play a pivotal role in the inflammatory response induced by CPB (5, 6). Moreover, the neutrophil to lymphocyte ratio (NLR) is a novel inflammatory marker which has been found to be associated with the severity and prognosis of many cardiovascular diseases (7).…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that, with or without sepsis, NGAL could be used as an early marker in neonatal AKI cases. (16) However, in a more recent study, Reiter et al (17) stated that plasma and urine NGAL levels were not reliable markers for developing AKI in neonates after cardiac surgery with cardiopulmonary bypass. In our study, there was no patient diagnosed with AKI.…”
Section: Discussionmentioning
confidence: 99%